2009
DOI: 10.1111/j.1743-6109.2008.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Transsexualism in Serbia: A Twenty-Year Follow-Up Study

Abstract: Introduction Gender dysphoria occurs in all societies and cultures. The prevailing social context has a strong impact on its manifestations as well as on applications by individuals with the condition for sex reassignment treatment. Aim To describe a transsexual population seeking sex reassignment treatment in Serbia, part of former Yugoslavia. Methods Data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 35 publications
5
62
0
6
Order By: Relevance
“…While many previous studies founded higher incidence of male to female transsexuals, compared to female to male transsexuals, our study shown the equal number [13]. So, it was interesting to compare the digit length ratio (2D : 4D) in our country and compare them with the results from other studies and controls.…”
Section: Introductionmentioning
confidence: 54%
“…While many previous studies founded higher incidence of male to female transsexuals, compared to female to male transsexuals, our study shown the equal number [13]. So, it was interesting to compare the digit length ratio (2D : 4D) in our country and compare them with the results from other studies and controls.…”
Section: Introductionmentioning
confidence: 54%
“…It was also observed that lesbian women with PCOS have higher levels of androgens compared to heterosexual women with PCOS. In Serbia, Vujovic et al (24) found a 14.4% prevalence of PCOS among female-to-male transsexuals, and it was higher than in the general population. Based on these results, it was suggested that high concentrations of androgens usually seen in patients with PCOS may contribute with sexual orientation.…”
Section: Discussionmentioning
confidence: 97%
“…Many previous studies suffer from low outcome ascertainment,[6], [9], [21], [29] whereas this study has captured almost the entire population of sex-reassigned transsexual individuals in Sweden from 1973–2003. Moreover, previous outcome studies have mixed pre-operative and post-operative transsexual persons,[22], [37] while we included only post-operative transsexual persons that also legally changed sex. Finally, whereas previous studies either lack a control group or use standardised mortality rates or standardised incidence rates as comparisons,[9], [10], [11] we selected random population controls matched by birth year, and either birth or final sex.…”
Section: Discussionmentioning
confidence: 99%